High Yield Transfer of Clean Large-Area Epitaxial Oxide Thin Films - Zhang, Bowen (Nanomicro Lett, 2021)
In this work, we have developed a new method for manipulating and transferring up to 5 mm × 10 mm epitaxial oxide thin films. The method involves fixing a PET frame onto a PMMA attachment film, enabling transfer of epitaxial films lifted-off by wet chemical etching of a Sr(3)Al(2)O(6) sacrificial layer. The crystallinity, surface morphology, continuity, and purity of the films are all preserved in the transfer process. We demonstrate the applicability of our method for three different film compositions and structures of thickness ~ 100 nm. Furthermore, we show that by using epitaxial nanocomposite films, lift-off yield is improved by ~ 50% compared to plain epitaxial films and we ascribe this effect to the higher fracture toughness of the composites. This work shows important steps towards large-scale perovskite thin-film-based electronic device applications. [Image: see text] SUPPLEMENTARY INFORMATION: The online version of this article (10.1007/s40820-020-00573-4).